Management of large tympanic membrane perforations – A comparative study - Saaketh Boddupalli; Sreenivas Gouripeddi (Journal of Clinical and Scientific Research)
Background: This study aimed to compare the results of tympanoplasty with temporalis fascia graft alone and with composite graft in cases of inactive mucosal-type chronic suppurative otitis media with subtotal and total perforations in graft uptake and hearing improvement. Methods: It is a prospective case–control study done in in our teaching hospital at Tirupati, in the Department of Ear, Nose and Throat. This study includes 30 patients who are divided into two groups by simple randomisation. Results: In the present study, the graft uptake rate when using only the temporalis fascia was 80% and that in the cartilage and temporalis fascia was 93.34%. Significant hearing improvement (>10 dB) was observed in 75% of patients in the temporalis fascia graft alone group and 71.4% in the composite graft group. There was a mean improvement in air conduction from pre-operative to post-operative in the tympanoplasty with temporalis fascia of 14.4 dB and in the tympanoplasty with composite graft group of 15.06 dB. Conclusions: In the case of large tympanic membrane perforations, the composite graft using the temporalis fascia graft along with conchal/tragal cartilage is superior to the temporalis fascia graft alone, with better graft uptake. However, hearing improvement was better in the group in which only the temporalis fascia graft was used.